When IEEE 802.11 and 5G Meet Time-Sensitive Networking - Mahin K. Atiq; Raheeb Muzaffar; Oscar Seijo; INaki Val; Hans-Peter Bernhard (IEEE Open Journal of the Industrial Electronics Society, 2022)
Many emerging applications require a higher level of flexibility, modularity, and efficiency but are dependent on advancements in communication infrastructure and distributed computing. Time-sensitive networking (TSN) standards aim at providing vendor agnostic, reliable, and deterministic communications over the Ethernet, but lack in flexibility and modularity provisions. In this context wireless communication systems are preferred given the obvious benefits in terms of increased flexibility, reduced deployment & maintenance costs, and inherent mobility support. However, the stochastic nature of the wireless medium poses several challenges in achieving these benefits. In this paper we comprehensively analyze the recent standardization efforts and developments in IEEE 802.11 and 5G to enable low-latency, deterministic communications and present the current status of their integration with wired TSN. Then, we present a set of use cases that may be enabled by wireless TSN including industrial automation, automotive, or audiovisual applications.